Empathy of Regular Junior High School Students on Children With Special Needs - Rheni Meiliani; Elisabet W. Hapsari (Laboratory of General Psychology, Faculty of Psychology, Universitas Surabaya, 2015)
Children with special needs (ABK) who are enrolled in regular (public) schools will elicit empathy or negative behavior, because regular students cannot comprehend and tolerate the behavior of the ABK. The aim of the present study is to investigate the relationship between empathy and attitude towards ABK on students of a regular junior high school in Surabaya. Subjects are 11-16 year old students (N = 25) who have interacted with an ABK, obtained through total population study. Data was collected with scales for attitude towards ABK and empathy, and was further analyzed with a non-parametric Kendall's Tau-b correlation. Results showed values for r = .229 and p = .124 (p >.5), indicating a lack of correlation between empathy and attitude towards ABK on regular students of the junior high school. This lack of correlation was argued to be because attitude includes a cognitive component that acts as a source of information, and empathy of an individual is objective and situational. It was further argued that external factors such as experience, culture, learning process, direct contact, and information can also contribute to the lack of relationship between the two variables. Descriptively, a majority of subjects have a moderately positive to very positive attitude (92%) and empathy towards ABK was categorized as very high (96%).